Belonging and Becoming in a Multicultural World - Moran, Laura (Rutgers University Press, 2021)
Children and youth are front and center in the context of global mass migration and the social discord around questions of multicultural inclusion that it often ignites. It is young people at the forefront of navigating the complexities of cultural and ethnic diversity in their everyday lives. Imprecise portrayals of their inclination to either embrace diversity or to incite racism are used to exemplify both the success and failures of the multicultural project. In the context of young people’s heightened politicization, Belonging and Becoming in a Multicultural World, shifts the focus to a group of Sudanese and Karen refugee youth’s own insights, explanations and practices as they attempt to create a sense of identity and belonging. It sees these young people engaging race, racism and national identity in creative and unexpected ways as they are confronted with the social and moral implications of multiculturalism in Australia.